Laser capture microdissection in combination with mass spectrometry: Approach to characterization of tissue-specific proteomes of Eudiplozoon nipponicum (Monogenea, Polyopisthocotylea). - Pavel Roudnický; David Potěšil; Zbyněk Zdráhal; Milan Gelnar; Martin Kašný (PLoS ONE, 2020)
Eudiplozoon nipponicum (Goto, 1891) is a hematophagous monogenean ectoparasite which inhabits the gills of the common carp (Cyprinus carpio). Heavy infestation can lead to anemia and in conjunction with secondary bacterial infections cause poor health and eventual death of the host. This study is based on an innovative approach to protein localization which has never been used in parasitology before. Using laser capture microdissection, we dissected particular areas of the parasite body without contaminating the samples by surrounding tissue and in combination with analysis by mass spectrometry obtained tissue-specific proteomes of tegument, intestine, and parenchyma of our model organism, E. nipponicum. We successfully verified the presence of certain functional proteins (e.g. cathepsin L) in tissues where their presence was expected (intestine) and confirmed that there were no traces of these proteins in other tissues (tegument and parenchyma). Additionally, we identified a total of 2,059 proteins, including 72 peptidases and 33 peptidase inhibitors. As expected, the greatest variety was found in the intestine and the lowest variety in the parenchyma. Our results are significant on two levels. Firstly, we demonstrated that one can localize all proteins in one analysis and without using laboratory animals (antibodies for immunolocalization of single proteins). Secondly, this study offers the first complex proteomic data on not only the E. nipponicum but within the whole class of Monogenea, which was from this point of view until recently neglected.